Analisis penggunaan emoji dalam percakapan di sosial media Whatsapp - Cahya, Intan Aulia; Pratiwi, Fanisa Ira Ronia; Muassomah, Muassomah (Maliki Interdisciplinary Journal, 2024)
Nowadays, numerous technologies N have been developed to facilitate daily life and fulfill everyday needs. Particularly in the field of communication, one notable example of this development is emoticons. This text aims specifically to map the emojis used by communicators and analyze various emojis on social media, particularly in WhatsApp chats. The method employed is a descriptive approach to depict the patterns of emoji usage and an exploratory approach to uncover the meanings and functions of emojis. Data collection was done through screenshots of WhatsApp chats. The findings of this research indicate that emojis are frequently used compared to other forms of communication and that there are several variations in the meanings of a single emoji, which further clarify the intended message. This study concludes that the use of emojis plays a significant role in digital communication by enriching emotional expressions and aiding in conveying messages accurately within limited contexts.